2020
DOI: 10.1021/acsami.0c11862
|View full text |Cite
|
Sign up to set email alerts
|

Facile Green Synthesis of Pseudocapacitance-Contributed Ultrahigh Capacity Fe2(MoO4)3 as an Anode for Lithium-Ion Batteries

Abstract: The investigation into the use of earth-abundant elements as electrode materials for lithium-ion batteries (LIBs) is becoming more urgent because of the high demand for electric vehicles and portable devices. Herein, a new green synthesis strategy, based on a facile solid-state reaction with the assistance of water droplets' vapor, was conducted to prepare Fe 2 (MoO 4 ) 3 nanosheets as anode materials for LIBs. The obtained sample possesses a two-dimensional stacked nanosheet construction with open gaps provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…According to the XRD results, the Fe 0.107 MoO x sample contained a lot of Fe 2 (MoO 4 ) 3 phase, which is suspected to be a reason for the decay of the catalytic effect. To verify this assumption, neat Fe 2 (MoO 4 ) 3 was prepared according to literature, and tested for its AODS activity, as shown in Figure b. The result revealed that Fe 2 (MoO 4 ) 3 was barely capable of catalytic activity, either.…”
Section: Resultsmentioning
confidence: 97%
“…According to the XRD results, the Fe 0.107 MoO x sample contained a lot of Fe 2 (MoO 4 ) 3 phase, which is suspected to be a reason for the decay of the catalytic effect. To verify this assumption, neat Fe 2 (MoO 4 ) 3 was prepared according to literature, and tested for its AODS activity, as shown in Figure b. The result revealed that Fe 2 (MoO 4 ) 3 was barely capable of catalytic activity, either.…”
Section: Resultsmentioning
confidence: 97%
“…In terms of green chemical synthesis, a novel approach based on water droplets vapor‐assisted solid‐state reaction has been implemented for the fabrication of Fe 2 (MoO 4 ) 3 nanosheets as anodes. [ 186 ] This methodology allows to get elevated surface area nanosheets with high reversible capacity at 100 mA g −1 under cycling (1983 mAh g −1 ) and may be caused by a pseudocapacitive effect. [ 186 ] Another promising material for anodes based on Li 2 Fe 3 O 5 microcrystals has been synthesized via single‐pot molten salt method for the obtention of octahedral crystals, a low cost method that is scalable and sustainable, [ 187 ] showing good values of capacity (604 mAh g −1 ) under cycling and high rate capability.…”
Section: Novel Green Synthesis Processesmentioning
confidence: 99%
“…[ 186 ] This methodology allows to get elevated surface area nanosheets with high reversible capacity at 100 mA g −1 under cycling (1983 mAh g −1 ) and may be caused by a pseudocapacitive effect. [ 186 ] Another promising material for anodes based on Li 2 Fe 3 O 5 microcrystals has been synthesized via single‐pot molten salt method for the obtention of octahedral crystals, a low cost method that is scalable and sustainable, [ 187 ] showing good values of capacity (604 mAh g −1 ) under cycling and high rate capability. In addition, a green hydrothermal synthesis route has been reported to fabricate spherical SiO/hard carbon SOHC nanocomposites and its nitrogenates for anodes, showing enhanced electrochemical properties like high capacity (1398 mAh g −1 ) and very high cycling stability in the nitrogenated SOHCs (1248 mAh g −1 for 500 cycles).…”
Section: Novel Green Synthesis Processesmentioning
confidence: 99%
“…These cells are the opposite of galvanic cells (batteries), called electrolyte cells. In these cells, unlike the battery, we give energy to force a reaction that is not thermodynamically desirable [ 60 ].…”
Section: Electrolyte Decomposition In the Anodementioning
confidence: 99%
“…It has been shown that using silicon nanotubes instead of nanowires is more effective. In nanotubes, the necessary space is provided for volume change on both sides of the inner and outer walls [34,[59][60][61]. In addition, nanotubes are usually thinner than nanowires, so transmitters are better, because silicon is a semiconductor and is also amorphous during the duty cycle due to stresses, it does not conduct well electronically during the duty cycle [47,48,54].…”
Section: Different Nano Morphologiesmentioning
confidence: 99%